ANALISIS KEPUASAN KONSUMEN TERHADAP LAYANAN DAN PRODUK BEBERAPA UMKM DI KOTA MEDAN - Fauzia Agustini; Dita Amanah; Dedy Ansari Harahap (Fakultas Ekonomi Universitas Negeri Medan, 2023)
This study aims to analyze consumer satisfaction with services and products at Hijabsunshine.co, Yasin Water Depot, 90 degree coffee and penyet chicken safa marwa. data was collected through interviews and distributing questionnaires to 30 respondents in each business, so that the total is 120 respondents. This research is quantitative descriptive. Data analysis was obtained from the frequency using the SPSS program. The results showed that in general the respondents expressed satisfaction with the services and products provided by Hijabsunshine.co, Yasin Water Depot, 90 degree coffee and penyet chicken safa marwa. researchers hope that every MSMEs in Medan City should continue to evaluate the services and products they provide in order to be able to satisfy consumers.